Temporal trends and outcomes in aortic and mitral valve surgery in Finland - Myllykangas, Monna (fi=Turun yliopisto|en=University of Turku|, 2022)
Aortic valve surgery is the most common type of heart valve surgery in western countries. The main causes for aortic valve surgery are aortic valve stenosis and regurgitation. Mitral valve regurgitation is the most common cause for mitral valve surgery, as mitral stenosis is rare. The proportion of mitral valve repairs has increased during the last decades. It is currently the primary choice for treating mitral valve disease of all etiologies. Cardiac surgery patients have sex-depended differences as to type of surgery and outcome. Women are usually older by the time of surgery, and the comorbidity burden differs between sexes. Results on outcome are conflicting. Thromboembolic prophylaxis is indicated for the first three months after biologic valve replacement. However, often the need for anticoagulation is long-term due to other conditions that increase the risk of thromboembolic complications. The aim of this study was to elucidate nationwide trends in mitral and aortic valve surgery in Finland. We also studied the sex differences in long-term outcomes after an aortic valve replacement procedure, and the prevalence and type of longterm oral anticoagulation treatment and their association with complications and death in patients who have undergone biological aortic valve replacement. We found that the proportion of mitral valve repair surgery and the use of bioprosthetic valves have increased. Short- and long-term mortality after mitral valve surgery has decreased. The basic characteristics of aortic valve patients have changed: patients are older, the proportion of women has decreased, and patients have markedly more comorbidities. The use of bioprosthetic aortic valves has increased and short-term mortality has improved while long-term mortality has remained unchanged. Sex is not an independent risk factor for long-term mortality after surgical aortic valve replacement. However, male-sex was associated with higher risk of bleeding, infective endocarditis, and re-surgery. The use of oral anticoagulation after biologic aortic valve replacement appears to be associated with decreased risk of death and increased risk of stroke.

Aortta- ja mitraaliläppäkirurgian pitkän aikavälin muutokset Suomessa Aorttaläppäkirurgia on tavallisin sydänkirurgian muoto länsimaissa. Tavallisimmat syyt aorttaläppäkirurgialle ovat aorttaläpän ahtauma ja vuoto. Mitraaliläppäkirurgian tavallisin syy on mirtaaliläpän vuoto. Mitraaliläpän ahtauma on nykyään harvinainen. Mitraaliläpän korjausleikkauksien osuus on noussut viimeisien vuosikymmenten aikana. Se on tällä hetkellä ensisijainen mitraaliläpän vajaatoiminnan hoitomuoto riippumatta aiheuttajasta. Sydänkirurgisilla potilailla tiedetään olevan sukupuolesta riippuvaisia eroja. Naiset ovat yleensä vanhempia leikkauksen aikaan, ja perussairauksien aiheuttama taakka eroaa sukupuolten välillä. Tulokset ennusteesta ovat vaihtelevia. Tromboosiprofylaksiaa suositellaan ensimmäisen kolmen kuukauden ajaksi biologisen aorttatekoläppäleikkauksen jälkeen. Kuitenkin antikoagulaation tarve on usein pitkäaikainen muiden tromboembolisia komplikaatioita aiheuttavien sairauksien johdosta. Tutkimuksemme tavoitteena oli selvittää mitraaliläpän korjaus- ja tekoläppäleikkauksen sekä aorttatekoläppäleikkauksen maanlaajuisia pitkäaikaismuutoksia ja -ennustetta Suomessa. Tavoitteena oli lisäksi tutkia sukupuolieroja pitkäaikaisennusteessa aorttatekoläppäleikkauksen jälkeen. Näiden lisäksi tutkimme pitkäaikaisantikoagulaation esiintyvyyttä ja tyyppiä biologisen aorttatekoläppäleikkauksen jälkeen. Totesimme, että biologisten läppäproteesien käyttö ja mitraaliläpän korjausleikkausten määrä lisääntyi. Mitraaliläppäkirurgian lyhyt- ja pitkäaikaiskuolleisuus on laskenut. Aorttaläppäpotilaiden taustaominaisuudet muuttuivat seuranta-aikana: potilaat ovat vanhempia, naisten osuus pieneni ja perussairauksien määrä kasvoi. Biologisten aorttaläppäproteesien käyttö lisääntyi, lyhytaikaiskuolleisuus vähentyi ja pitkäaikaisennuste pysyi ennallaan. Sukupuoli ei ole itsenäinen pitkäaikaiskuolleisuuden riskitekijä aorttatekoläppäleikkauksen jälkeen. Miehillä on suurentunut riski vuotokomplikaatioille, infektiiviselle endokardiitille ja uusintaleikkaukselle. Suun kautta otettavien antikoagulanttien pitkäaikaiskäyttö aortan biologisen tekoläppäleikkauksen jälkeen vaikuttaisi liittyvän vähentyneeseen kuolemariskiin ja lisääntyneeseen aivohalvausriskiin.